2010
DOI: 10.1103/physrevlett.104.173901
|View full text |Cite
|
Sign up to set email alerts
|

Light-Mode Condensation in Actively-Mode-Locked Lasers

Abstract: We show that the formation of pulses in actively mode-locked lasers exhibits in certain conditions a transition of the laser mode system to a light pulse state that is similar to Bose-Einstein condensation (BEC). The study is done in the framework of statistical light-mode dynamics with a mapping between the distribution of the laser eigenmodes to the equilibrium statistical physics of noninteracting bosons in an external potential. The light-mode BEC transition occurs for a mode-locking modulation that has a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 24 publications
0
46
0
Order By: Relevance
“…(1) discussed above have been realized with periodic boundary conditions in the transverse variable r; i.e., the incoherent wave (14), (15) and refers to the WT regime beyond the thermodynamic limit (μ = 0), while the dashed black line refers to the thermodynamic limit [μ → 0inEqs. (14)and (15) ψ(z,r) is expanded in the plane wave Fourier basis. Although this corresponds to the usual numerical approach to study wave condensation [19][20][21]33], recently, a more realistic physical configuration has been considered in which the incoherent wave propagates in a mutimode optical waveguide [22].…”
Section: Waveguide Geometrymentioning
confidence: 99%
See 2 more Smart Citations
“…(1) discussed above have been realized with periodic boundary conditions in the transverse variable r; i.e., the incoherent wave (14), (15) and refers to the WT regime beyond the thermodynamic limit (μ = 0), while the dashed black line refers to the thermodynamic limit [μ → 0inEqs. (14)and (15) ψ(z,r) is expanded in the plane wave Fourier basis. Although this corresponds to the usual numerical approach to study wave condensation [19][20][21]33], recently, a more realistic physical configuration has been considered in which the incoherent wave propagates in a mutimode optical waveguide [22].…”
Section: Waveguide Geometrymentioning
confidence: 99%
“…The study of the nonlinear evolution of incoherent optical waves is a subject of growing interest in various fields of investigations, including, e.g., wave propagation in homogeneous [1][2][3][4][5][6][7][8] or periodic media [9], nonlinear imaging [10], cavity systems [11][12][13][14][15], or nonlinear interferometry [16]. In particular, the analysis of the long-term evolution of nonlinear incoherent optical waves has been considered in various circumstances [1][2][3]6,8], as well as in various optical media characterized by different nonlinearities [4,5,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a different perspective, optical cavities and lasers offer an interesting experimental platform to study different regimes of optical turbulence [12,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. In particular, the phenomenon of condensation of photons has been recently demonstrated in optical microcavities [38], which raised important questions such as the relation between lasing and condensation [39].…”
Section: Introductionmentioning
confidence: 99%
“…It is thus easy to establish a parallel between ML and BoseEinstein condensation of cold atoms [5], which is governed by the same equation. In fact, it has been recently demonstrated that in some cases mode locking is a form of condensation of classical waves [6][7][8] that, if treated in the framework of a thermodynamic approach, is a form of phase transition [9].…”
Section: Introductionmentioning
confidence: 99%